Paramagnetic Ionic Liquid/Metal Organic Framework Composites for CO2/CH4 and CO2/N2 Separations - Ferreira, Tiago J.; Vera, Ana T.; de Moura, Beatriz A.; Esteves, Laura M.; Tariq, Mohammad; Esperança, José M. S. S.; Esteves, Isabel A. A. C. (Frontiers in Chemistry, 2020)
Global warming is arguably the biggest scientific challenge of the 21st century and its environmental consequences are already noticeable. To mitigate the emissions of greenhouse gases, particularly of CO2, there is an urgent need to design materials with improved adsorbent properties. Five different magnetic ionic liquids were impregnated into the metal–organic framework ZIF-8. The composites were produced by a direct-contact method, and their performance as sorbents for gas separation applications was studied. The impact of the ionic liquid anion on the sorption capacity and ideal CO2/CH4 and CO2/N2 selectivities were studied, focusing on understanding the influence of metal atom and ligand on the adsorbent properties. Reproducible methodology, along with rigorous characterization, were established to assess the impact of the ionic liquid on the performance of the composite materials. Results show that the ionic liquid was well impregnated, the ZIF-8 structure was maintained after ionic liquid impregnation. The produced composites were of microporous nature and were thermally stable. CO2, CH4 and N2 adsorption–desorption isotherms were obtained at 303 K and between 0-16 bar. The adsorption-desorption data of the composites were compared with that obtained for original ZIF-8. The general trend in composites is that the increased gas uptake per available pore volume compensates the pore volume loss. Adsorption data per unit mass showed that composites have reversible sorption, but inferior gas uptake at all pressure ranges. This is due to the observed total pore volume loss by the ionic liquid pore occupation/blockage. In most cases, composites showed superior selectivity performance at all pressure range. In particular, the composite [C4MIM]2[MnCl4]@ZIF-8 shows a different low-pressure selectivity trend from the original MOF, with a 33% increase in the CO2/N2 selectivity at 1 bar and 19% increase in the CO2/CH4 selectivity at 10 bar. This material shows potential for use in a post-combustion CO2 capture application that can contribute to greenhouse gas mitigation.